RESOLUTION OF CUTANEOUS LEISHMANIASIS AFTER ACUTE ECZEMA DUE TO INTRALESIONAL MEGLUMINE ANTIMONIATE - Vasconcellos, Erica de Camargo Ferreira e; Pimentel, Maria Inês Fernandes; Valete-Rosalino, Cláudia Maria; Madeira, Maria de Fátima; Schubach, Armando de Oliveira (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
We report a case of a 42 year-old female, who came to a leishmaniasis reference center in Rio de Janeiro, Brazil, presenting a cutaneous leishmaniasis lesion in the right forearm. Treatment with low-dose intramuscular meglumine antimoniate (MA) (5 mg Sb5+/kg/day) was initiated, with improvement after 28 days, although with the development of generalized eczema. After 87 days, the lesion worsened. Patient refused treatment with amphotericin B. MA was then infiltrated in the lesion, in two sessions, resulting in local eczema, with bullae formation; however, twenty days after, both the ulcer and eczema receded. Intralesional administration of MA should be used carefully when previous cutaneous hypersensitivity is detected.